Exploring barriers to vasectomy adoption among married men in Dadra and Nagar Haveli - Patel, Ronak Dhirubhai; Dabhelker, Monika M.; Patel, Priya Mahendrabhai; Solanki, Preeti (Publishing Office of the University of Rzeszow, 2024)
Introduction and aim. Vasectomy was introduced in India in 1992 and is the most effective, simple, and safe permanent method of contraception yet its use is very limited among the population. The study’s objectives were to assess the knowledge, attitude, and perception towards vasectomy and the barriers to adoption among married men in Dadra and Nagar Haveli. Material and methods. A cross-sectional hospital-based study was conducted on married male attendants of patients and data were collected on sociodemographic details, knowledge regarding vasectomy, their attitude and perceptions towards vasec tomy, and their intention of using vasectomy in the future. Results. Out of 300 participants, 258 (86%) participants have heard of vasectomy as a contraceptive method, and only one participant has undergone vasectomy. The majority (285; 95%) of the participants agreed that family planning is also a responsi bility of males while nearly two-third (185; 61.7%) of them were not willing to undergo vasectomy in the future. Procedure-re lated factors, post-procedure-related factors, social factors, availability of alternate contraceptive methods, and preference for tubectomy were the barriers to the adoption of vasectomy. Conclusion. There is a need to provide correct information and counseling about vasectomy and non-scalpel vasectomy to eligible couples to increase the acceptance of vasectomy as a safe, effective, and cheaper method of contraception.
Permission was obtained from the Institutional Ethics Committee (DMHS/IEC/2016/214/1237) before commencing the study and written informed consent was obtained from every participant prior to their recruitment into the study. To ensure confidentiality, the identities of the respondents have been kept anonymous. Following the interviews, participants received counseling and comprehensive health education on vasectomy, including its benefits.
Keywords: attitude; barriers; knowledge; married men; perception; vasectomy